Deciphering water oxidation catalysts: the dominant role of surface chemistry over reconstruction degree in activity promotion - An, Li (2025)
Water splitting hinges crucially on the availability of electrocatalysts for the oxygen evolution reaction. The surface reconstruction has been widely observed in perovskite catalysts, and the reconstruction degree has been often correlated with the activity enhancement. Here, a systematic study on the roles of Fe substitution in activation of perovskite LaNiO3 is reported. The substituting Fe content influences both current change tendency and surface reconstruction degree. LaNi0.9Fe0.1O3 is found exhibiting a volcano-peak intrinsic activity in both pristine and reconstructed among all substituted perovskites in the LaNi1-xFexO3 (x = 0.00, 0.10, 0.25, 0.50, 0.75, 1.00) series. The reconstructed LaNi0.9Fe0.1O3 shows a higher intrinsic activity than most reported NiFe-based catalysts. Besides, density functional theory calculations reveal that Fe substitution can lower the O 2p level, which thus stabilize lattice oxygen in LaNi0.9Fe0.1O3 and ensure its long-term stability. Furthermore, it is vital interesting that activity of the reconstructed catalysts relied more on the surface chemistry rather than the reconstruction degree. The effect of Fe on the degree of surface reconstruction of the perovskite is decoupled from that on its activity enhancement after surface reconstruction. This finding showcases the importance to customize the surface chemistry of reconstructed catalysts for water oxidation.